Construction of an index tracker for debt sustainability assessment in the Philippines - Armin Paul D. Allado; Lance Nicklaus S. Lim; Nerie Angelie T. Tulauan; Marvin Kyle M. Abreu; Patricia Louise M. Agabin; Joaquin Charles D. Regio (Asian Development Bank Institute (ADBI), 2022)
With economies around the world facing more dire challenges as an immediate result of the COVID-19 pandemic, the need for national governments to borrow funds has grown. The abrupt increase in debt level highlights the importance of implementing suitable models to project emerging debt scenarios and assessing debt sustainability. Given that sustainable debt levels vary from country to country, this study applied the IMF's Debt Sustainability Analysis to assess the Philippines' debt burden over time to be used as an input in the construction of a debt index tracker that incorporates other relevant fiscal and economic indicators. The index tracker serves as an aggregate barometer on whether debt levels have breached the sustainable threshold level. Furthermore, the study will utilize the debt tracker to show the implicit debt ceiling and the available fiscal policy room that can respond to the next potential shock.
Keywords: H63; 330; debt sustainability; Debt Index tracker; sustainable debt threshold level; implicit debt ceiling; available fiscal space